Changing Trends in the World of Literature during Covid 19 (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The corona period is one of the most difficult times in the history of mankind. It was a time of uncertainty as we could not really predict the future of humanity. Before the corona pandemic, we believed that epidemics were a thing of the past as our medical science and technology had advanced to the extent that our doctors and scientists could handle any epidemic, but that belief had been shattered during this pandemic. In India a catastrophic situation has arisen due to overpopulation and ignorance. The doctor to population ratio in India is 1:1456 while the World Health Organization recommends a ratio of 1:1000. The current situation in India is caused by a number of factors. It was a time when human fears were at their peak, as we were forced to rely on technology because of the coronavirus pandemic. Somehow, this proved to be a huge loss in human connection. On the surface, technology seemed to be reducing the distance between people, allowing us to communicate with our loved ones even if they were far away from us. But on a deeper level, we realized that this technology forced us to live in a world of virtual reality and thus proved to be the reason for the emptiness of human connection, as we began to mistake real sacrifices for virtual ones.